Effectiveness of quality improvement on occurrence of needle stick injuries (NSIs) in Harare city, Zimbabwe, 2017: A quasi-experimental study - Sithole Zvanaka; Kudzai Masunda; Collen Madembo; Chonzi Prosper; Stanely Tapesana; Shecriton Muguza; Olufemi Ajumobi; Lilian Bulage; Tsitsi Juru; Notion Tafara Gombe; Gerald Shambira; Mufuta Tshimanga (Journal of Interventional Epidemiology and Public Health)
Introduction: Globally, healthcare workers (HCWs) incur an estimated two million needle stick injuries (NSIs) per year and 90% of these injuries occur in Africa. In Zimbabwe, neither the prevalence nor the factors associated with HCW-acquired NSI are known. Harare city recorded an increase in NSIs among nurses from 1% in 2013 to 7% in 2016, highest being from the Southern District. We designed and evaluated the effectiveness of a quality improvement (QI) approach towards reduction of NSI incidence. Methods: We conducted a quasi-experimental study purposively among 83 nurses in southern District. We designed and implemented an intervention package comprising training, deployment of social behavioral change materials and workflow re-organisation. We measured effectiveness of the intervention using Plan, Do Check Act cycle. Data on intervention effectiveness was collected pre and six months post-implementation, using structured questionnaires. Analysis was presented with frequencies, means, and proportions. Results: Lack of knowledge 99% (82/83), unorganised activities 60% (50/83) and limited space in the treatment rooms 59% (49/83), were the major reasons for NSI before intervention. Pre-intervention, 10% (8/83) of the nurses had good knowledge level while 96% (80/83) had good knowledge level post- intervention. The NSI incidence rates pre-intervention was 0.97 NSI/month and 0.17 NSI/month post-intervention, a decline rate of 82% (p< 0.01). Total cost saved by the intervention was $5 777.00. Conclusion: Lack of knowledge on occurrence of NSI, unorganised activities, and limited working space in the treatment rooms were the major reasons for NSIs before the intervention. The QI intervention was effective in reducing incidence of NSI. We recommend HCW trainings on NSI, promotion of socio-behavioral change and workflow re-organisation in order to offset economic efforts directed at managing NSIs.